Tetralogy of Fallot with isolated levocardia in a young female - Zeeshan Sattar; Hafez Muhammad Abdullah; Sohaib Roomi; Waqas Ullah; Adnan Khan; Ali Ghani; Asrar Ahmad (Greater Baltimore Medical Center, 2019)
Tetralogy of Fallot is the most common cyanotic congenital heart disease. It consists of right ventricular outflow tract obstruction, a ventricular septal defect, abnormally located aorta and right ventricular hypertrophy. It usually occurs as an isolated anomaly with a normally placed heart and abdominal viscera. We present a case of a 19 years old female who presented with a prolonged history of shortness of breath (SOB) and cyanosis. After undergoing echocardiography and cardiac computed tomography angiogram (CTA), she was diagnosed to be a case of Tetrology of Fallot (TOF) in association with situs inversus with levocardia also termed 'isolated levocardia'. The patient underwent surgical correction and she was asymptomatic with no residual cardiac defects on follow up after 6 months. Isolated levocardia is a rare condition that is usually associated with severe cardiac defects and a low life expectancy in untreated patients. It is unusual for it to be diagnosed in adults as in our case.